Mental Health Status of Patients Attending Avicenna Infertility Clinic - Z Behjati Ardakani; MM Akhondi; K Kamali; Z Fazli Khalaf; Sh Eskandari; B Ghorbani (JRI, 2010)
Background: Infertility bears a painful psychological distress and affected couples’ reaction to it is commonly seen in the form of anxiety, depression, somatization or social dysfunction. The goal of this study was to evaluate the mental health status of the infertile couples referred the Avicenna Infertility Clinic by the General Health Questionnaire-28 (GHQ-28). Methods: In this qualitative study, 400 couples were randomly selected among couples referred to Avicenna Infertility Clinic for infertility work-up and treatment. After signing an informed consent form, each individual filled a questionnaire on demo-graphic characteristics and one for mental health status assessment, the GHQ- 28. Results: The mean age of the couples (21 to 63 years) was 34  6 years. The prelimin-ary diagnosis of infertility related to gender included 21.9% female, 65.5% male, 7.1% both and 5.4% unexplained causes of infertility. By regarding a cut-off point of 24 for the GHQ-24 questionnaire, 4% of the individuals showed an abnormal score. The abnormal scores were in domains of social dysfunction (43.5%), anxiety (10.9%), somatization (9.5%) and depression (3.3%). Significant statistical difference were seen between male and female participants in total GHQ-28 scores, as well as somatization and depression, (p < 0.05), where the female participants showed worse psychological health states (p < 0.05). Conclusion: About 4% of the infertile patients attending Avicenna Infertility Clinic seem to be at risk of psychological disorders and provision of psychological health care alongside the medical treatment is advisable.
Keywords: Anxiety, Depression, General health questionnaire, Infertility, Social dysfunction, Somatization